Decision indicators for urban old community renewal: a multi-stakeholder approach in Guangze, China - Xin Liu; Yuanyang Zhao; Congyue Wang (Journal of Asian Architecture and Building Engineering)
In the context of urban stock renewal, urban old community renewal (UOCR) has gradually shifted from incremental expansion to improving quality and efficiency, with a significant emphasis on Stakeholder Value Creation (SVC) and the sustainability of renewal efforts. However, community renewal still faces the risk of formalism. Based on the Delphi method and the Analytic Hierarchy Process (AHP), this study explores how to construct a sustainable community renewal decision-making framework under the collaboration of stakeholders through the Guangze case study. Firstly, focus group discussions and resident questionnaire surveys identified 37 indicators related to old community renewal. Secondly, a weighted decision-making framework was developed using the Delphi method and AHP, comprising indicators from three dimensions: infrastructure renewal, functional facility improvement, and service operation construction. The findings demonstrate that collaborative discussions among multiple stakeholders supported the construction of the decision-making model and revealed urban old community renewal indicators that had been overlooked in previous studies. These proposed indicators can serve as meaningful references and provide practical paradigms and decision-making support for urban renewal strategies at both local and national levels.